1000 First Days of Life As An Effort to Prevention and Prevention Stunting in Rw 08 North Margahayu - Liliek Fauziah; Henni Purnasari; Asysyifa Riana; Tri Ardayani (CV Media Inti Teknologi, 2023)
Chronic malnutrition can lead to stunting. Stunting is caused by insufficient nutritional intake for a long time due to feeding that is not in accordance with nutritional needs during pregnancy, infancy and toddlerhood. Prevention of stunting through the first 1000 days of life (HPK) as an effort to overcome and prevent stunting was carried out in RW 08 North Margahayu Village, Caringin Subdistrict, Bandung City with lecture and question and answer methods and provision of additional food. The tools and materials used were Power point, leaflets and examples of nutritious food or the contents of my plate and examples of food for MP - breastfeeding children. The implementation of this counseling activity was carried out on September 22, 2022 starting at 08.00 until completion at Posyandu RW 08 North Margahayu Village. The targets of this activity are pregnant women, mothers of infants and toddlers and Posyandu cadres. The results of these activities obtained distribution based on the age of counseling activities mostly in the age range of 20-30 years as much as 73, 53%, and the results on the level of knowledge at Posyandu RW 08, namely the level of knowledge about the First 1000 Days of Life is in the moderate category, namely 38.23%, in the Good category, namely 35.29%, and the category is less, namely 26.47%.